Treble Damage Awards in Private Lawsuits for Price Fixing - Salant, Stephen W. (Journal of Political Economy, 1987)
The traditional model for assessing the effects of treble damage pena lties on price fixing is reexamined and shown to yield surprising res ults. Unless the probability of detection is extremely sensitive to the price charged, increasing the damage multiple will affect neither market efficiency nor expected distribution, and will raise the mark et price. Copyright 1987 by University of Chicago Press.